Breast Tumor Detection Using Classification Algorithm (International Journal of Innovative Research in Computer Science & Technology, 2021)
Breast cancer is the most common cancer  in women. It is the leading cause of cancer death in  developing countries and the second leading cause of  cancer death in women in the United States, behind only  lung cancer. Females are more likely to develop breast  cancer. However, in a few instances, it is clear that males  have also been affected. Breast cancer has been  discovered. [1] Breast tumors may be either cancerous or non- cancerous.  Benign tumors are easily treated with doctor-prescribed  medications. Malignant tumors are a sign of a high risk of  breast cancer and should be removed as soon as possible.  Early identification and treatment of tumor lowers the  risk of cancer-related death. The survival rate of breast  cancer patients in America has been reported to be 90%  in recent years, but it is as low as 60% in India. [2]  The key cause of this shortcoming is late tumor diagnosis  and classification, which causes treatment delays. Using  machine learning to perform a task will reduce the  workload of physicians and radiologists. According to  research, doctors can only diagnose breast cancer with a  79 percent accuracy rate, while machines can diagnose it  with a 91 percent accuracy rate. Early diagnosis is the  best way to increase the chance of treatment and chance  of survival.
Keywords: Malignant; Benign; Diagnosis; Radiologist; Survival; Tumors